Better essence than jumble: Text thinning in the context of the attention economy and digital edition - Cordón-García, José-Antonio (Anuario ThinkEPI, 2017)
The recent changes in digital publishing have given rise to new developments in content creation, production, and consumption. In some cases these changes have affected preexisting functions, genres, or trends, which now have a different role in the digital environment. In others, new products have been generated that relate to the new environments and are, therefore, far from their printed reference. One of these changes is related to narrative. On the one hand, there has been a gradual thinning of the conventional narrative genres, and on the other, business models have been launched based on short texts, short stories, and short novels. In addition, new genres have emerged as twitnovels, blognovels, microfiction, etc., which have found their natural environment in the digital media. These phenomena are an example of the paradox between a supply of content that grows exponentially coupled with less and less availability of leisure time to consume them, so that competition occurs for the prevalence of one over others in a context of economy of attention and specialization of discourses.